(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
In this paper, we assumed the Halo nucleus consist of a nuclear core and two neutrons in the framework of the cluster model, and we wrote the Hamiltonian that expresses the relative motion of nucleons in the cluster model using Jacobi coordinates. The above radius was determined in supra-spherical polar coordinates. We get Fadeev’s equations by switching the wave function in the Schrödinger equation. The calculations were carried out for the T-form of Borromean halo nuclei with the model (core + two neutrons). The values are in agreement to the experimental values.